PERBANDINGAN KADAR INTERLEUKIN 6 PADA PERSALINAN PRETERM DAN KEHAMILAN NORMAL - Visti Delvina; Arni Amir; Ermawati Ermawati (Maternal Child Health Care, 2022)
Preterm labor occurs between 20 weeks and before 37 weeks of pregnancy. It is indicated by regular contractions of the uterus and it may cause the thinning and flattening of the cervix. Preterm labor also causes the high rates of perinatal morbidity and mortality. Increasing levels of interleukin 6 during pregnancy can stimulate the preterm labor. The design of this reseacrh was a comparative cross sectional study. It was conducted in Rasidin District Hospital, Siti Rahmah Hospital and Biomedical Laboratory, Faculty of Medicine, Andalas University, Padang on March to June 2018. There were 50 samples in this reseach. It was selected by consecutive sampling. The samples were divided into two groups: preterm labor and normal pregnancy. The interleukin 6 levels were examined by the ELISA method. Then, the data were analyzed by using the t test. The results of this reseach showed that the mean level of IL-6 in the preterm labor group was 90.22 ± 21.41ng / L. Then, 75.57 ± 14.01 ng / L for the mean level of IL-6 in the normal pregnancy group with p= 0.006. Moreover, statistical test inffered that there were significant differences between IL-6 levels in preterm labor and normal pregnancy. In short, it can be concluded that IL-6 levels in the preterm labor group were higher than normal pregnancy group.Keywords: IL-6 levels, preterm labor